Calico spy - Brownley, Margaret (Brownley, Margaret. Undercover ladies, 2016)
"Pinkerton operative Katie Madison s newest case takes her to Calico, Kansas, where two Harvey House restaurant waitresses were murdered in mysterious circumstances. Calico s sheriff, Branch Whitman, has never met a Pink he liked and is stunned to learn the pretty redhead's true identity as she works undercover as a Harvey girl. A tornado hits town, and a past deception puts Branch s eight-year-old-son in danger. Now the Sheriff has no choice but to work with Katie or chance losing everything he holds dear."--www.amazon.com